Defesa técnica e juizados especiais cíveis: estudo comparado entre o modelo jurídico brasileiro e o norte-americano - Cirilo Augusto Fiuza Saldanha de Vargas (2019)
There is no longer place, in the vanguard Civil Procedural Law, for the formal exercise of the principle of adversary. The procedural dialectic, previously treated as “audience bilaterality”, assumed a dynamic or material character, taking into account the power of influence of the party in the conduct of the procedure, in the definition of the best instructional strategy and, consequently, in the elaboration of the legitimate judicial decision. Within the modern procedural methodology, technical defense has a prominent position. The Advocacy and the Public Defender’s Office – qualified by the 1988 Constituent Assembly as Essential Functions for the Administration of Justice – provide litigators with legal assistance, adding concreteness to the contradictory participation. In other words, the granting of postulatory capacity to the professional holding legal technical knowledge constitutes a public guarantee that access to the judicial protection of fundamental rights does not acquire contours of mere symbolism or rhetoric. Unfortunately, due to the cultural subservience of the Brazilian legislature, accustomed to the a priori importation of foreign legal models, without proper certainty of efficiency in the State of origin, was incorporated into the Brazilian civil procedural system the North American procedure for the settlement of disputes of low repercussion (from which derives the model of the small claims courts), which relativizes the importance of technical defense. Therefore, under the justification of ensuring economy, celerity and debureaucratization, formal access to justice was institutionalized, contrary to the due process of law.